2016
DOI: 10.1177/0145721716658357
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Home-Based Diabetes Prevention and Management Program on High-Risk American Indian Youth

Abstract: The TOD program was feasible, acceptable, and effective in lowering diabetes risk among reservation-based American Indian youth. It is the first efficacious youth-focused diabetes prevention and management program developed and implemented in partnership with tribal communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 48 publications
0
41
0
Order By: Relevance
“…Differences in blood glucose control were measured in 15 studies. Of these, four studies found no differences, while 11 studies found improvements in glycaemic control . Improvements in physical activity or greater adherence to behavioural support were reported in all studies that had measured physical activity .…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Differences in blood glucose control were measured in 15 studies. Of these, four studies found no differences, while 11 studies found improvements in glycaemic control . Improvements in physical activity or greater adherence to behavioural support were reported in all studies that had measured physical activity .…”
Section: Resultsmentioning
confidence: 94%
“…Nine studies had measured body mass index (BMI) scores. Of these, eight found greater reductions in BMI in the intervention group than controls . One study found no impact on BMI …”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations